Effects of the incorporation of bithiophene instead of thiophene between the pyrrolo[3, 4-c]pyrrole-1, 3-dione units of a bis(pyrrolo[3, 4-c]pyrrole-1, 3-dione)-based polymer for polymer solar cells. (1st November 2016) - Tamilavan, Vellaiappillai; Kim, Seungmin; Sung, Ji Yeong; Lee, Dal Yong; Cho, Shinuk; Jin, Youngeup; Jeong, Junghyun; Park, Sung Heum; Hyun, Myung Ho
Abstract : The effect of a connecting spacer unit on the properties of bis(pyrrolo[3, 4- c ]pyrrole-1, 3-dione)-based polymers was studied. Abstract : A new wide band gap polymer, P(BDTT–BTBDPPD), consisting of electron rich 4, 8-bis(5-(2-ethylhexyl)thiophen-2-yl)benzo[1, 2- b :4, 5- b ′]dithiophene (BDTT) and electron deficient bithiophene-incorporated bis(pyrrolo[3, 4- c ]pyrrole-1, 3(2 H, 5 H )-dione) (BTBDPPD) derivative was prepared to improve the photovoltaic performances of a reported polymer, P(BDTT–TBDPPD), containing BDTT and thiophene-incorporated bis(pyrrolo[3, 4- c ]pyrrole-1, 3(2 H, 5 H )-dione) (TBDPPD) derivative. Polymer P(BDTT–BTBDPPD) exhibited maximum absorption at 478 nm and the calculated optical band gap was 2.10 eV. The highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) energy levels of P(BDTT–BTBDPPD) were estimated to be −5.44 eV and −3.34 eV. The hole mobility of P(BDTT–BTBDPPD) was 3.22 × 10 −4 cm 2 V −1 s −1 . The polymer solar cells (PSCs) prepared using P(BDTT–BTBDPPD) : PC70 BM (1 : 2 wt%) + 3 vol% DIO blend offered a maximum power conversion efficiency (PCE) of 4.62% with an open-circuit voltage ( V oc ) of 0.90 V, a short-circuit current ( J sc ) of 7.99 mA cm −2, and a fill factor (FF) of 64%. This study suggests that the replacement of the thiophene spacer unit located between the pyrrolo[3, 4- c ]pyrrole-1, 3(2 H, 5 H )-dione units of bis(pyrrolo[3, 4- c ]pyrrole-1, 3(2 H, 5 H )-dione) derivative with a bithiophene unit did not considerably alter the energy levels and charge transport properties of the resulting polymer. However, the overall photovoltaic performance was improved due mainly to the enhanced morphology of the photoactive layer.